2014
DOI: 10.1128/aem.00807-14
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Enterocytozoon bieneusi in Asymptomatic Pigs and Assessment of Zoonotic Risk at the Genotype Level

Abstract: bEnterocytozoon bieneusi is an emerging and clinically significant enteric parasite infecting humans and animals and can cause life-threatening diarrhea in immunocompromised people. Pigs are considered to be one of the main reservoir hosts of E. bieneusi based on their high prevalence rates and zoonotic genotypes in pigs. As an opportunistic pathogen, E. bieneusi infection of pigs can be inapparent, which leads to neglect in detecting this parasite in pigs and assessing the epidemiological role of pigs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 47 publications
(88 reference statements)
7
56
1
Order By: Relevance
“…These studies suggest that pigs might be a source of human microsporidiosis and water pollution. Moreover, EbpC may represent the main cause of human microsporidiosis in China [21, 2325]. Our results confirm this possibility by demonstrating the potential for the zoonotic transmission of E. bieneusi .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…These studies suggest that pigs might be a source of human microsporidiosis and water pollution. Moreover, EbpC may represent the main cause of human microsporidiosis in China [21, 2325]. Our results confirm this possibility by demonstrating the potential for the zoonotic transmission of E. bieneusi .…”
Section: Resultssupporting
confidence: 81%
“…1), which suggests their zoonotic potential. Among them, the human-pathogenic genotype EbpC was the most prevalent, which has been frequently found in hospitalized children in Shanghai, HIV+ and HIV- people in Henan, wastewater in four cities, and pigs in multiple cities in China [1, 21, 2325, 45, 46]. These studies suggest that pigs might be a source of human microsporidiosis and water pollution.…”
Section: Resultsmentioning
confidence: 95%
“…The prevalence of E. bieneusi found in this study (59.3%) was higher than those reported in other studies worldwide [18,24,26,40,56,63,66,67,[71][72][73][74], with exception of two studies, one in the Czech Republic, where 94% of 79 pigs were found E. bienesi-positive [37] and one in China, where 83.2% and 89.5% of the 95 pigs studied were positive for E. bienesi using SSU rRNA or ITS genes, respectively [65].…”
Section: Discussioncontrasting
confidence: 81%
“…In one farm in the present study, 5 of 7 pigs examined were infected with this zoonotic genotype ( Table 2). This genotype was also the most prevalent in a study conducted in 95 healthy pigs in China; 79 pigs were found E. bieneusi positive with EbpA genotype identified in 30 of them [65]. This genotype is also the only genotype found in this study that has been previously reported in Brazil.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation